ANALISIS FINANSIAL DAN KELAYAKAN USAHATANI SALAK PONDOH DI DESA TIGA JUHAR KECAMATAN STM HULU KABUPATEN DELI SERDANG - M. Wasito (JASA PADI, 2018)
Hulu District, Deli Serdang Regency. This research was conducted in Tiga Juhar Village, STM Hulu District, which was deliberately chosen as the location of the study because it was the center of the production of salak pondoh in Deli Serdang . The number of respondents was 60 farmers who were taken randomly with a simple random sampling system. The research method used in this study is a survey method, data collection was carried out in April 2018. The purpose of this study was answered quantitatively by using financial analysis Net B / C. NPV, IRR, PBP and sensitivity analysis using a 9% factor discount. The results showed that salak pondoh farming in Tiga Juhar Village, STM Hulu District was financially feasible and profitable to continue. This refers to the value of the Net B / C = 3.5, value.of NPV = 116,953,200. Value of IRR = 20.6% and PBP = 4 years 8 months. Salak pondoh farming is sensitive to decreasing production and decreasing production prices but not sensitive to rising fertilizer prices.